2022
DOI: 10.3389/fpls.2022.1080745
|View full text |Cite
|
Sign up to set email alerts
|

Visible and near-infrared spectroscopy and deep learning application for the qualitative and quantitative investigation of nitrogen status in cotton leaves

Abstract: Leaf nitrogen concentration (LNC) is a critical indicator of crop nutrient status. In this study, the feasibility of using visible and near-infrared spectroscopy combined with deep learning to estimate LNC in cotton leaves was explored. The samples were collected from cotton’s whole growth cycle, and the spectra were from different measurement environments. The random frog (RF), weighted partial least squares regression (WPLS), and saliency map were used for characteristic wavelength selection. Qualitative mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…It was the first study applied to pistachio tree leaves and also included the estimation of multiple macro-and microelements in contrast to studies with only one or several nutrient elements. Xiao et al (2022) tested an NIRS system and deep learning technique to assess leaf nitrogen concentration (LNC) of fresh cotton leaves, and they found a good accuracy of up to 83% to classify the leaves into three LNC groups. Phanomsophon et al (2022) showed that the NIRS method provided good accuracy (>80%) for the classification of N, P, and K concentration levels of durian fruit tree leaves and stated that they obtained higher accuracy with fresh leaf samples than dried-ground leaf samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was the first study applied to pistachio tree leaves and also included the estimation of multiple macro-and microelements in contrast to studies with only one or several nutrient elements. Xiao et al (2022) tested an NIRS system and deep learning technique to assess leaf nitrogen concentration (LNC) of fresh cotton leaves, and they found a good accuracy of up to 83% to classify the leaves into three LNC groups. Phanomsophon et al (2022) showed that the NIRS method provided good accuracy (>80%) for the classification of N, P, and K concentration levels of durian fruit tree leaves and stated that they obtained higher accuracy with fresh leaf samples than dried-ground leaf samples.…”
Section: Discussionmentioning
confidence: 99%
“…Xiao et al. (2022) tested an NIRS system and deep learning technique to assess leaf nitrogen concentration (LNC) of fresh cotton leaves, and they found a good accuracy of up to 83% to classify the leaves into three LNC groups. Phanomsophon et al.…”
Section: Discussionmentioning
confidence: 99%
“…This is why an important trend is now rising as it relates to the measure of N content on plants from image analysis. Most of the time these approaches use multispectral images to classify the N content of different crops, including maize ( Nguyen et al 2023 ; Wijewardane et al 2023 ), cotton ( Xiao et al 2022 ), or sorghum ( Wijewardane et al 2023 ).…”
Section: Nitrogen Research In the Age Of Artificial Intelligence (Ai)mentioning
confidence: 99%